Unraveling the two decades of Knowledge Hiding scholarship: A systematic review, bibliometric analysis, and literature synthesis - Hafiz Muhammad Usman Khizar; Rashid Khurshid; Mohammed A. Al-Waqfi (Journal of Innovation & Knowledge (JIK), 2024)
Purpose - This study aims to provide a state-of-the-art review of the literature on Knowledge Hiding (KH), focusing on its inherent knowledge structure (i.e. intellectual, social, and conceptual structure). This study also presents an integrative synthesis of previous research and highlights knowledge gaps and limitations for further knowledge advancement in this field. Methodology - The systematic literature review approach was used to identify, select, and review the extant KH literature. For analysis, we employed a hybrid technique that combines quantitative and qualitative methods. In the first phase, we conducted quantitative bibliometric analyses (using VOS viewer and Biblioshiny in R-Studio) to highlight the state of the research profile. In the second phase, we utilise the ADO-TCM framework to synthesise the current literature into key themes, followed by the proposal of future research trajectories. Results - Our findings in the first phase highlighted the current research profile of KH in terms of publication timeline, relevant journals, utilised methods, top contributing authors, affiliations, and countries. In addition, our first-phase findings revealed the knowledge structure of KH research: intellectual structure (i.e. influential authors, influential studies, and citation analysis), social structure (i.e. collaborating authors, institutions, and countries), and conceptual structure (i.e. co-citation analysis, keyword co-occurrences, and thematic mapping). In the second phase, we discuss the KH literature and propose a future research agenda regarding antecedents, decisions, and outcomes (ADO) and theories, contexts, and methods (TCM) frameworks. Future Research / Implications - By offering a knowledge database of existing literature and building a solid foundation for future research, this study is anticipated to inspire academics and researchers to expand the literature on this topic and theoretically develop the field. Additionally, it creates a strong argument for businesses to acknowledge the presence of KH and assess the risks, advantages, and drawbacks of this phenomenon in order to make wise decisions.
Keywords: M12; M50; 650; Knowledge hiding; Bibliometric; Knowledge management; ADO-TCM; Systematic literature review